NK cell exhaustion in Wilson’s disease revealed by single-cell RNA sequencing predicts the prognosis of cholecystitis - Jin, Yong; Xing, Jiayu; Dai, Chenyu; Jin, Lei; Zhang, Wanying; Tao, Qianqian; Hou, Mei; Li, Ziyi; Yang, Wen; Feng, Qiyu; Wang, Hongyang; Yu, Qingsheng (eLife, 2024)
Metabolic abnormalities associated with liver disease have a significant impact on the risk and prognosis of cholecystitis. However, the underlying mechanism remains to be elucidated. Here, we investigated this issue using Wilson’s disease (WD) as a model, which is a genetic disorder characterized by impaired mitochondrial function and copper metabolism. Our retrospective clinical study found that WD patients have a significantly higher incidence of cholecystitis and a poorer prognosis. The hepatic immune cell landscape using single-cell RNA sequencing showed that the tissue immune microenvironment is altered in WD, mainly a major change in the constitution and function of the innate immune system. Exhaustion of natural killer (NK) cells is the fundamental factor, supported by the upregulated expression of inhibitory receptors and the downregulated expression of cytotoxic molecules, which was verified in clinical samples. Further bioinformatic analysis confirmed a positive correlation between NK cell exhaustion and poor prognosis in cholecystitis and other inflammatory diseases. The study demonstrated dysfunction of liver immune cells triggered by specific metabolic abnormalities in WD, with a focus on the correlation between NK cell exhaustion and poor healing of cholecystitis, providing new insights into the improvement of inflammatory diseases by assessing immune cell function.